Treatment Experience of 210 Pediatric Patients With Extraordinary Daytime Urinary Frequency: A Prospective Study - Li, Yan; Zhang, Ying; Liu, Chao; Li, Xiang; Zhou, Qi; Sun, Chao; Zhang, Lei (Frontiers in Pediatrics, 2021)
Background: Lactulose can be used to manage chronic constipation and children who are withholding their bowel movements, but no studies are available regarding lactulose to treat pediatric extraordinary daytime urinary frequency (PEDUF). To explore the benefits of different therapeutic regimens (non-drug treatment vs. oral lactulose) in patients with PEDUF. Methods: This prospective study included PEDUF patients admitted to the Pediatric Center of Qilu Hospital of Shandong University (Qingdao) from January 2015 to December 2019. The patients randomized received non-drug treatment (counseling), drug treatment (lactulose), or combination therapy. A therapeutic effect was defined by a decrease of>10% of the urination frequency. Results: A total of 210 patients were included. They were 5.9±0.4 years. There were 98 boys and 112 girls. Among the 210 patients, 82.4% (173/210) of their family members reported symptoms of constipation. Among the three groups, the response rate was 61.4% (43/70) in the non-drug treatment group, 90.0% (63/70) in the drug treatment group, and 91.4% (64/70) in the combination therapy group (P<0.0001). Conclusion: The frequency of constipation in children with PEDUF is high. The use of a laxative, like lactulose, might achieve a high therapeutic response rate in children with PEDUF, higher than counseling alone. That might represent a valuable therapeutic strategy for PEDUF.